Downstream Evolution of Particulate Organic Matter Composition From Permafrost Thaw Slumps - Keskitalo, Kirsi H.; Bröder, Lisa; Shakil, Sarah; Zolkos, Scott; Tank, Suzanne E.; van Dongen, Bart E.; Tesi, Tommaso; Haghipour, Negar; Eglinton, Timothy I.; Kokelj, Steven V.; Vonk, Jorien E. (Frontiers in Earth Science, 2021)
Permafrost soils, which store almost half of the global belowground organic carbon (OC), are susceptible to thaw upon climate warming. On the Peel Plateau of northwestern Canada, the number and size of retrogressive thaw slumps (RTS) has increased in recent decades due to rising temperatures and higher precipitation. These RTS features caused by the rapid thaw of ice-rich permafrost release organic matter dominantly as particulate organic carbon (POC) to the stream network. In this study, we sampled POC and streambank sediments along a fluvial transect (∼12 km) downstream from two RTS features and assessed the composition and degradation status of the mobilized permafrost OC. We found that RTS features add old, Pleistocene-aged permafrost POC to the stream system that is traceable kilometers downstream. The POC released consists mainly of recalcitrant compounds that persists within stream networks, whereas labile compounds originate from the active layer and appear to largely degrade within the scar zone of the RTS feature. Thermokarst on the Peel Plateau is likely to intensify in the future, but our data suggest that most of the permafrost OC released is not readily degradable within the stream system and thus may have little potential for atmospheric evasion. Possibilities for the recalcitrant OC to degrade over decadal to millennial time scales while being transported via larger river networks, and within the marine environment, do however, still exist. These findings add to our understanding of the vulnerable Arctic landscapes and how they may interact with the global climate.